Psychedelic: An Illustration that Reveals False Power in Rhythm 0 Performance Art - Dewanto, Thomas Hanandry; Bahruddin, Muhammad (Mudra Jurnal Seni Budaya, 2024)
The performance art entitled Rhythm 0 by Marina Abramovic is controversial, raising various questions regarding its power and influence in the context of art. This research aims to illustrate the microphysical approach to power in the performing arts Rhythm 0, where power emerges from fear and shifts to the dominance of the ideology of power. A qualitative approach with visual analysis techniques was used in this research to explain the phenomenon of this performing arts from a very subjective view. This created illustration entitled "Psychedelic" reveals false powers in the form of intense hallucinations involving auditory, visual and feeling experiences in the Rhythm 0. The basic principles of art were used as the basis for creating this illustrative work. In this case, the use of gold leaf, peony flower elements and halos in the illustration also has a solid symbolic value, so semiotics is used as a basis for giving meaning to the symbols used. The results of this research show that the apparent power contained in the Rhythm 0 performing arts can be revealed through an illustration entitled "Psychedelic", which describes the context of the artwork in depth. This research contributes to understanding Rhythm 0’s artwork and enriches knowledge about using psychedelic illustrations as a medium for artistic expression. This research also highlights how these illustrations can communicate complex themes in the performing arts, strengthening our understanding of power dynamics in arts contexts.